Pseudolesion in the right parafissural liver parenchyma on CT: The base is found in embryology and collagen content. - Willemijn M Klein; Lianne J P Sonnemans; Sabine Franckenberg; Barbara Fliss; Dominic Gascho; Mathias Prokop; Wouter H Lamers; Jill P J M Hikspoors; Michael J Thali; Patricia M Flach (PLoS ONE, 2020)
Background Computed tomography (CT) images of livers may show a hypo-attenuated structure alongside the falciform ligament, which can be a focal fatty pseudolesion and can mimic a malignancy. The preferred location is on the right parafissural site, ventral in segment IVa/b. The etiology is not clear, nor is it known how the histology of this location develops. These are evaluated in this study. Methods 40 adult cadavers with autopsy and / or postmortem CT in a university hospital and a forensic center were included. Liver biopsies were taken at the left side of the falciform ligament as control, and at the right side as the possible precursor of a pseudolesion; these were examined for collagen and fat content. Cadavers with steatotic (>5% fat) or fibrotic (>2% collagen) control samples were excluded. Results Significantly more collagen was present in the right parafissural liver parenchyma: median 0.68% (IQR: 0.32-1.17%), compared to the left side 0.48% (IQR: 0.21-0.75%) (p 0.008), with equal fat content and CT attenuation values. The etiophysiology goes back to the demise of the umbilical venes in the early embryonic and neonatal period. Conclusions The right parafissural area contains more collagen and an equal amount of fat compared to the control left side. This supports the hypothesis of delayed, 'third' inflow: the postnatal change in blood supply from umbilical to portal leaves the downstream parafissural area hypoperfused leading to hypoxia which in turn results in collagen accumulation and the persistence of paraumbilical veins of Sappey.